2008
DOI: 10.1002/lt.21603
|View full text |Cite
|
Sign up to set email alerts
|

Temporary portocaval shunt in orthotopic liver transplantation: Need for a standardized approach?

Abstract: Maintenance of portal and systemic venous return during the anhepatic phase of liver transplantation (LT) improves hemodynamic stability. With the piggyback technique, caval return is maintained; however, temporary clamping of the portal vein is still necessary. The use of a temporary portocaval shunt (TPCS) has been proposed to minimize the effect of portal venous interruption. The aim of this study was to perform a systematic review of the literature to determine whether there is evidence to support the rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…We find early creation of a temporary portocaval shunt very useful to reduce bleeding as well as avoid splanchnic congestion. 8 The first anastomosis at implantation of the graft is the outflow anastomosis (Figure 3). The next anastomosis is the portal vein anastomosis and it is important to ensure no redundancy and anastomotic narrowing is avoided by leaving a growth factor.…”
Section: Vascular Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We find early creation of a temporary portocaval shunt very useful to reduce bleeding as well as avoid splanchnic congestion. 8 The first anastomosis at implantation of the graft is the outflow anastomosis (Figure 3). The next anastomosis is the portal vein anastomosis and it is important to ensure no redundancy and anastomotic narrowing is avoided by leaving a growth factor.…”
Section: Vascular Complicationsmentioning
confidence: 99%
“…Ensuring integrity of the blood supply to the biliary tree, transecting the bile ducts along with the hilar plate and refinement in techniques of biliary anastomosis in LDLT has resulted in a significant reduction in the incidence of biliary complications from 24.3-40.6% before 2007 to 5. [3][4][5][6][7][8][9][10][11][12].8% in studies published after 2008 (Table 6). [27][28][29][30][31][32][33][34] Overall biliary complications in LDLT in our series was seen in three recipients (16.6%) which compares well with other studies.…”
Section: Biliary Complicationsmentioning
confidence: 99%
“…However, that study failed to show an improvement in graft function in the TPCS group, probably due to the limited sample size (40 patients in each group) with almost no ECD grafts. Other studies have confirmed the benefit of TPCS on blood transfusion, intraoperative hemodynamic status, and reduction of reperfusion syndrome incidence . As for graft outcome and function, Ghinolfi et al reported their series of 148 OLTs and found a significant reduction in 30‐day mortality in the TPCS group and in 3‐month mortality when the patients received high‐risk donor grafts.…”
Section: Discussionmentioning
confidence: 89%
“…The exact mechanisms underlying the protective properties of a temporary portocaval shunt still remain unknown. However, recent studies have reported beneficial effects of using a portocaval shunt, as enhanced portal blood flow has been shown to be associated with reduced liver injury following post‐reperfusion hemodynamic instability . Some mediators released from the gut, such as proinflammatory cytokines, endotoxin, and chemokines, caused by splanchnic congestion, may be responsible for the observed liver injury in patients without a shunt.…”
Section: Discussionmentioning
confidence: 99%